Internet connectivity disruption in Vietnam (Vietnam) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Vietnam. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: VN-2026-0064. Severity: critical. Confidence: 67%